Pengaruh Penerapan Observasi dan Konseling Ringan Terhadap Kepuasan Kerja di PT. Lion Super Indo Basilica - Rina Octaviana; Alfina Damayanti (Jurnal Riset Multidisiplin Edukasi, 2025)
This Field Work Practice (PKL) Report documents the implementation of a light counseling program that was observed at PT Lion Super Indo Basilica, Palembang. This program was designed to address various operational problems that affect employee job satisfaction. SWOT analysis was used as an analysis method to evaluate the program's strengths, weaknesses, opportunities, and threats. The results showed significant changes in several aspects of performance. Communication between teams became more effective, accuracy in work increased, and store operational efficiency improved. Several employees reported that the counseling sessions helped them understand their respective roles and responsibilities, and encouraged work motivation. However, the implementation of the program faced several limitations, such as the limited number of participants (10-20 employees) due to lack of human resources and short implementation time.